Wire rope isolators for vibration isolation of equipment and structures - A review - Balaji, P.; Rahman, Muhammad; Moussa, L.; Lau, Hieng Ho (2015)
© Published under licence by IOP Publishing Ltd. Vibrations and shocks are studied using various techniques and analyzed to predict their detrimental effect on the equipment and structures. In cases, where the effects of vibration become unacceptable, it may cause structural damage and affect the operation of the equipment. Hence, adding a discrete system to isolate the vibration from source becomes necessary. The Wire Rope Isolator (WRI) can be used to effectively isolate the system from disturbing vibrations. The WRI is a type of passive isolator that exhibits nonlinear behavior. It consists of stranded wire rope held between two metal retainer bars and the metal wire rope is made up of individual wire strands that are in frictional contact with each other, hence, it is a kind of friction-type isolator. This paper compiles the research work on wire rope isolators. This paper presents the research work under two categories, namely monotonic and cyclic loading behaviors of WRI. The review also discusses the different terminologies associated with vibration isolation system and highlights the comparison between various isolation systems.